2009
DOI: 10.1007/s10665-009-9312-0
|View full text |Cite
|
Sign up to set email alerts
|

Invariance and first integrals of continuous and discrete Hamiltonian equations

Abstract: In this paper we consider the relation between symmetries and first integrals for both continuous canonical Hamiltonian equations and discrete Hamiltonian equations. We observe that canonical Hamiltonian equations can be obtained by variational principle from an action functional and consider invariance properties of this functional as it is done in Lagrangian formalism. We rewrite the well-known Noether's identity in terms of the Hamiltonian function and symmetry operators. This approach, based on symmetries … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
49
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 40 publications
0
49
0
Order By: Relevance
“…Hamiltonian symmetries in evolutionary or canonical form have been considered ( [18]). Furthermore, symmetry properties of the Hamiltonian action have been investigated in the space (t, q, p) by [19] and [20]. In the latter, the authors considered the general form of the symmetries (7) and provided a Hamiltonian version of Noether's theorem.…”
Section: A Hamiltonian Version Of the Noether-type Theoremmentioning
confidence: 99%
See 1 more Smart Citation
“…Hamiltonian symmetries in evolutionary or canonical form have been considered ( [18]). Furthermore, symmetry properties of the Hamiltonian action have been investigated in the space (t, q, p) by [19] and [20]. In the latter, the authors considered the general form of the symmetries (7) and provided a Hamiltonian version of Noether's theorem.…”
Section: A Hamiltonian Version Of the Noether-type Theoremmentioning
confidence: 99%
“…The following important results which are analogs of Noether symmetries and the Noether theorem (see [18,21,22,20] for a discussion) were established.…”
Section: A Hamiltonian Version Of the Noether-type Theoremmentioning
confidence: 99%
“…This corresponds of course to a completely standard case (cf. [5,35]; see also [15] for a different approach to the searching for first integrals and their relation with symmetry properties a ).…”
Section: Symmetries and First Integrals Of Hamiltonian Equations Of Mmentioning
confidence: 99%
“…a It can be noted that all examples of symmetries given in [15] which admit a first integral belong to case (i) and those with no first integral belong to case (ii) below.…”
Section: Symmetries and First Integrals Of Hamiltonian Equations Of Mmentioning
confidence: 99%
“…In [92], there is consideration of the relationship between symmetries and first integrals (conservation laws) for both continuous and discrete Hamiltonian equations. It is shown that canonical Hamiltonian equations can be obtained through a variational principle from an action functional.…”
Section: Invariance and First Integrals Of Continuous And Discrete Hamentioning
confidence: 99%